2021
DOI: 10.2478/ctra-2021-0007
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Potential of Art Workshop: An Attempt to Foster People’s Creativity in an Online Environment

Abstract: Recently, the importance of creativity in society has been clearly recognized. Furthermore, educational practices through art, such as the STEAM paradigm, are being implemented gradually. However, the framework of how creativity should be fostered through art has not been sufficiently discussed. Based on studies of artists’ creative expertise, this study proposed a framework for fostering creativity through art. In addition, we conducted a year-long art program based on this framework in an online environment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 36 publications
(46 reference statements)
0
5
0
1
Order By: Relevance
“…This solution is also promising for the development of creativity. Online interventions are effective in shaping creative skills and related characteristics, as evidenced in an art workshop series [74]. Such effects might extend to large-scale creative collaboration and co-creation when considering theoretical literature that emphasizes the distributed nature of creativity in online environments [60], and case studies like r/place that revealed how certain aspects like community organization unravel during a creative project.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This solution is also promising for the development of creativity. Online interventions are effective in shaping creative skills and related characteristics, as evidenced in an art workshop series [74]. Such effects might extend to large-scale creative collaboration and co-creation when considering theoretical literature that emphasizes the distributed nature of creativity in online environments [60], and case studies like r/place that revealed how certain aspects like community organization unravel during a creative project.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, users would soon form communities to realize their common goal of creative activity: they started painting together, while also competing with other users (communities) for contested spots within the canvas. On a smaller scale, online art workshops were shown to lead to higher openness for others and their opinions, lower creativity anxiety, higher prevalence of pursuing everyday creative activities, and creative potential [74], underlining the potential of such interactive settings in online environments as a source for creative learning.…”
Section: Collaboration and Co-creation: A Creative Selfiementioning
confidence: 99%
See 1 more Smart Citation
“…Take for example, combinatorial creativity. The cognitive load of combining different objects mentally is enough that while it may be that the imagination would function better without the associated constraints of reality, in a combinatorial task having actual objects to play with inspires people to create more creative products (Shimizu & Okada, 2021). Playing with the real means that combinations which have no roots in memory or experience can be generated and these may break creative fixation (Valle´e-Tourangeau et al, 2011).…”
Section: In Relation To Creative Cognitionmentioning
confidence: 99%
“…En la siguiente fase, compartir, los participantes se reúnen en salas más pequeñas para trabajar en grupos de unos seis estudiantes. Si los es-tudiantes pueden ver varias pantallas al mismo tiempo (como se puede hacer con el software de videochat Zoom), generan más ideas (Shimizu et al, 2021). En la última fase, reflexión, los participantes vuelven a la sala principal y comparten lo que han aprendido.…”
Section: Colaboración En La Nubeunclassified